PENERAPAAN POJOK UMKM UNTUK KATALOG PRODUK CRAFT DAN FASHION PADA KOMUNITAS PPKM KAB.BANDUNG - Heru Nugroho; Wardani Muhamad; Agus Maolana Hidayat; Kristina Sisilia; Astadi Pangarso Nugroho; Robbi Hendriyanto (Jurnal Abdimas Bina Bangsa, 2023)
In facing the ban on gathering due to the Covid-19 pandemic, MSMEs in the Craft and Fashion sectors in Bandung who are members of the Paguyuban Pengusaha Kecil dan Menengah (PPKM) community need to find alternative ways to market their products. One effective solution is to use an online catalog. Through online catalogs, MSMEs can easily and effectively display their products through online platforms that can be accessed by many people. This allows MSMEs to expand their market and increase product visibility widely. In addition, the use of online catalogs also helps MSMEs save on marketing costs, increase efficiency in managing businesses, and establish connections with potential customers. Thus, the implementation of online catalogs is an important strategy in marketing and business development for MSMEs in Craft and Fashion